PROSES PRODUKSI PROGRAM ISLAM PEDIA DI SALAM TV (International Forum of Researchers and Lecturers, 2023)
This study aims to understand the Production Process of the Islamic Pedia Program at Salam TV Jl. Darmo, Ujung Serdang, Kec. Tj. Morawa, Deli Serdang Regency, North Sumatra. The research method used is a qualitative approach, using 1 informant as sources for data collection. The results obtained from this study are that the production process for the Islam Pedia program on Salam TV has several production stages, namely the pre-production process, the production process and the post-production process. In the pre-production process, the creative team drafted the concept, created the title, created the script, prepared materials starting from pictures and videos. The production stage is searching for photos from Google and videos from YouTube at sources that are trusted to be edited and combined with voice recordings (vo), this is done to support the script that has been written according to the theme being discussed. The post-production stage is uploading videos (media publicity) by the broadcast team (MCR) to YouTube, official Instagram greeting TV and other official websites and conducting evaluations through feedback from the public.